Aplica??o dos princ?pios da adapta??o baseada em ecossistemas (AbE) na concep??o de habita??es populares: uma proposta de interven??o para Feira de Santana - Bahia - Fiuza, ?dla Larissa Gomes (2023)
The intervention work presented has as its central objective the development of a conceptual model project of popular housing based on strategies of Adaptation based on Ecosystems. In this work the project is aimed at the needy population living in a risk area in the city of Feira de Santana, specifically in the Avi?rio neighborhood, in a locality with proximity to the Suba? river canal. For this it was necessary to understand the concept of the Adaptation strategy based on Ecosystems, its applicability, as well as its nexus with climate change, extreme weather events and the vulnerability of urban areas to this scenario. In addition, it was necessary to carry out site visits and the choice of a stretch for the analysis of the intervention, which was decisive for the application of strategies not only in the housing, but also in the surroundings. Based on an intervention project that worked on resilience and adaptation to climate change, the methodological procedures used were based on bibliographic research, fieldwork and realization of the project in computer programs. As a result, a project was obtained in AutoCad that was also represented in a 3D perspective and through illustrations in order to complement each other. At the end, budget tables were prepared that demonstrated the feasibility of implementing adaptation strategies and a comparison with the final cost between standard projects and with AbE application applied to the study area.